ADVANCEMENTS IN CANCER PHARMACOTHERAPY: TARGETED THERAPIES AND IMMUNOTHERAPY STRATEGIES, A REVIEW - MAQBOOL , H; YASIN , U; SHAWAL , L; ZULFIQAR , F; FATIMA , N; HASAN , W; NASIM , H; ISMAIL , M; RAFIQ , MA (Biological and Clinical Sciences Research Journal, 2024)
The development of immunotherapy and targeted medicines has fundamentally changed and revolutionized the field of cancer treatment. These cutting-edge methods, which include cancer vaccines, CAR-T cell therapy, checkpoint inhibitors, monoclonal antibodies, and small molecule inhibitors, are not only therapeutic interventions but also revolutionary instruments. They are carefully crafted to interfere with particular molecular pathways that propel tumors’ growth and spread and use patients’ immune systems to fight cancerous cells. This research aims to thoroughly investigate the mechanisms, clinical uses, efficacy, obstacles, current developments, and prospects of these noteworthy achievements in cancer pharmacotherapy. The paradigm changes in cancer, combining immunotherapy and targeted medicines, provide individualized treatment plans that consider each patient’s particular needs, offering a sense of reassurance and confidence in the treatment process.